Microwave fragmentation of a synthetic alundum-pyrite ore. Issue 3 (1st October 2020) - Yang, W.; Pickles, C.A.; Forster, J.
ABSTRACT: In the mining industry, the comminution process is very inefficient in terms of energy utilisation. Numerous research studies have investigated the use of microwave pre-treatment to fracture ore, prior to subsequent unit operations, such as grinding, flotation and leaching, therefore saving on energy consumption. The objective of the present work was to investigate the microwave fragmentation of a synthetic ore with controllable composition and particle size. The synthetic ore was composed of both a hyperactive material (pyrite) and an active material (alundum cement), which were compacted into a briquette. Heating behaviour, permittivity and thermogravimetric/differential thermal analysis (TGA/DTA) studies were conducted in order to understand the fundamental interactions of powdered samples with microwaves. The briquettes were processed in a microwave system followed by compression testing and image analysis to determine the effects of microwaving on the failure load and the fragmentation degree. It was found that the failure load of the briquettes decreased and the fragmentation degree increased with increasing pyrite particle size, pyrite content, and microwave energy absorption.